The Problems of Ensuring Information Security in Conditions of Uncertainty - Elena RYABOVA; Olga FILIPPOVA; Yulia MUNIROVA (Communications of International Proceedings, 2022)
In modern conditions, it is important for enterprises to be prepared for the changes in the external environment that occur frequently, irregularly, almost unpredictably, and also in conditions of constant growth of information threats and risks to achieve their goals in a timely manner. The article discusses the problems of ensuring information security, taking into account the influence of uncertainty parameters, presents conceptual approaches to ensuring information security and reducing environment uncertainty.
Keywords: Information Security; Information Technologies; Risk and Uncertainty.